2019
DOI: 10.1111/liv.14205
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease alters expression of genes governing hepatic nitrogen conversion

Abstract: Background & Aims We recently showed that the functional capacity for ureagenesis is deficient in non‐alcoholic fatty liver disease (NAFLD) patients. The aim of this study was to assess expression of urea cycle‐related genes to elucidate a possible gene regulatory basis to the functional problem. Methods Liver mRNA expression analyses within the gene pathway governing hepatic nitrogen conversion were performed in 20 non‐diabetic, biopsy‐proven NAFLD patients (8 simple steatosis; 12 non‐alcoholic steatohepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…In support of this, hypermethylation of promoter regions of the urea cycle genes Otc and Cps1 has been reported both in animals models of NASH and in patients with NAFLD [ 30 ]. In addition to Cps1 , two amino acid transporters, Slc7a2 and Slc38a2 , were downregulated in mice on HFD + FW as well as in Gcgr −/- mice, which is in line with human data showing downregulation in patients with NAFLD [ 31 , 46 ]. SLC38A2 transports neutral amino acids (i.e., alanine), and, in support of its possible role in the liver-alpha cell axis, transcription of Slc38a2 was increased in rats by feeding a high-protein diet, by glucagon administration, and in hepatocytes incubated with forskolin (an activator of adenylyl cyclase) [ 47 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In support of this, hypermethylation of promoter regions of the urea cycle genes Otc and Cps1 has been reported both in animals models of NASH and in patients with NAFLD [ 30 ]. In addition to Cps1 , two amino acid transporters, Slc7a2 and Slc38a2 , were downregulated in mice on HFD + FW as well as in Gcgr −/- mice, which is in line with human data showing downregulation in patients with NAFLD [ 31 , 46 ]. SLC38A2 transports neutral amino acids (i.e., alanine), and, in support of its possible role in the liver-alpha cell axis, transcription of Slc38a2 was increased in rats by feeding a high-protein diet, by glucagon administration, and in hepatocytes incubated with forskolin (an activator of adenylyl cyclase) [ 47 ].…”
Section: Discussionsupporting
confidence: 80%
“…It was recently shown that patients with non-alcoholic fatty liver disease (NAFLD) have reduced capacity for ureagenesis [ 29 ], and that gene expression of urea cycle-related enzymes is downregulated in NAFLD patients [ 30 , 31 ]. To test whether this is also the case in mice, animals were fed a high-fat diet and 15% fructose water (HFD + FW) for 8–10 weeks to induce a physiologically relevant model of hepatic steatosis ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…(3,31,32) Glucagon's impact on ureagenesis includes transcriptional changes in genes (such as carbamoylphosphate synthase 1 [CPS1], glutamic-oxaloacetic transaminase 1 [GOT1], and solute carrier family 25 member 18 [SLC25A18]) that regulate hepatic nitrogen conversion in NAFLD, as has been shown in HOMA-IR Glucagon-alanine index R 2 = 0.165 P < 0.05 several studies. (26,33,34) Eriksen et al (34) found that the genes most involved with urea cycle-related enzymes were down-regulated in patients with both NAFL and NASH compared to lean and obese controls without NAFLD. The altered expression explains the decrease observed in in vivo functional capacity for ureagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired urea cycle in fatty liver disease has been reported previously. (29)(30)(31)(32) The capacity of urea synthesis is decreased in patients with compromised liver function but increases in patients with inflammation. (33) Interestingly, both mechanisms are involved in alcoholic hepatitis.…”
Section: Discussionmentioning
confidence: 99%